2014
DOI: 10.1021/am501502v
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Ratiometric Sensor for Trace Vapor Detection of Hydrogen Peroxide

Abstract: Trace vapor detection of hydrogen peroxide (H2O2) represents a practical approach to nondestructive detection of peroxide-based explosives, including liquid mixtures of H2O2 and fuels and energetic peroxide derivatives, such as triacetone triperoxide (TATP), diacetone diperoxide (DADP), and hexamethylene triperoxide diamine (HMTD). Development of a simple chemical sensor system that responds to H2O2 vapor with high reliability and sufficient sensitivity (reactivity) remains a challenge. We report a fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 65 publications
(91 reference statements)
0
45
0
Order By: Relevance
“…Initial efforts using boronate groups for H 2 O 2 include an arylboronic ester‐based fluorescent probe that uses coumarin as the fluorescent reporter to detect H 2 O 2 in solution due to the structural cleavage to release the fluorescence of coumarin . Recently, Zang and co‐workers constructed fluorescent probes that were capable of detecting trace H 2 O 2 in vapor. A small‐molecular fluorescent “turn‐on” probe, based on an arylboronic ester naphthalimide unit for H 2 O 2 sensing was utilized .…”
Section: Fluorescent Probes For the Detection Of Ros‐related Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial efforts using boronate groups for H 2 O 2 include an arylboronic ester‐based fluorescent probe that uses coumarin as the fluorescent reporter to detect H 2 O 2 in solution due to the structural cleavage to release the fluorescence of coumarin . Recently, Zang and co‐workers constructed fluorescent probes that were capable of detecting trace H 2 O 2 in vapor. A small‐molecular fluorescent “turn‐on” probe, based on an arylboronic ester naphthalimide unit for H 2 O 2 sensing was utilized .…”
Section: Fluorescent Probes For the Detection Of Ros‐related Diseasesmentioning
confidence: 99%
“…A small‐molecular fluorescent “turn‐on” probe, based on an arylboronic ester naphthalimide unit for H 2 O 2 sensing was utilized . Subsequently, a ratiometric fluorescent probe was synthesized, exhibiting a subtle emission change in fluorescence intensity by H 2 O 2 ‐mediated oxidation of the boronate fluorophore ( Figure ). The presence of H 2 O 2 resulted in a redshift in fluorescence emission intensity.…”
Section: Fluorescent Probes For the Detection Of Ros‐related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] These compounds are powerful chromophores with remarkable fluorescence properties, [9] which found different applications in the last years. [10] We have recently introduced diaminoterephthalates as colored moleculars caffolds bearing up to four sites for orthogonal functionalization. [11] Furthermore, withp rerequisite functionalization, the fluorescencec an be switched on by ac hemical reaction and therefore, thesec ompounds can be used as "turn-on" probes for biochemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated the emergence of fluorescence-based methods, attracting great interest because of their sensitivity, selectivity, fast response, and ease of use [9][10][11]. However, there still exists a challenge of developing a simple, highly sensitive, and inexpensive platform for the rapid detection of H 2 O 2 [12,13].…”
Section: Introductionmentioning
confidence: 99%